Additifs alimentaires : Inventaire des substances ajoutées aux denrées alimentaires de large consommation dans l’Ouest algérien - Zakaria Lotfi Guaouar; Fatima Zahra Besseguir; Mira Gharbi; Imane Kecir (Journal de la Faculté de Médecine d'Oran)
Abstract Introduction- Food additives are used to extend the shelf life of prepared foods or to sweeten a beverage, for example. In this study, we present an overview of the food additives used in foodstuffs marketed in the city of Oran (West Algeria). Materials and methods- A descriptive cross-sectional study was carried out at the supermarkets and general food stores of the city of Oran to list the food additives incorporated in some foods of wide consumption. Results- A total of 114 food additives were identified. All the inventoried additives are listed in the Algerian official journal N°30 of 16 May 2012.The additives listed are not without risks to the health of the consumer. Some additives such as caramel dye or SIN150d are found in 3 local cookie brands and 4 local beverage brands (17.5%); sodium benzoate or SIN211 in 12 beverage brands and 2 jam brands (16.09%); butylhydroxyanisol (BHA) or SIN320 in a brand of chocolate, margarine and chips (1.67%).Overall, the labels of the products comply with the Algerian regulations with the exception of some shortcomings such as the nature of the aroma that was not always specified. Conclusion- The study found significant use of food additives. The level of risk on consumer health requires a broad awareness of the consumer, in particular moderate consumption of industrially prepared foodstuffs.